Oromandibular dystonia seen during pramipexole treatment: A rare case - Kara, Fatma; Göl, Mehmet Fatih; Varlıbaş, Ayhan (Journal of Surgery and Medicine, 2022)
Dystonia is an abnormal, often repetitive, bending/twisting behavioral disorder characterized by continuous or intermittent muscle contraction. Oromandibular dystonia (OMD) is a type of dystonia involving chewing, mouth circumference, tongue, and platysma muscles. OMD is divided into different clinical types, including jaw opening OMD, jaw closing OMD, and mixed type OMD. OMD may either be primary or secondary to other diseases. The average patient age is between 50 and 60 years, and several studies have shown that it is more common among women. Dystonia may occur either as idiopathic (primary) or resulting from neurodegenerative diseases and other secondary dystonia. OMD can cause difficulty in speaking, chewing, and swallowing and produce pain during these movements. Therefore, OMD can lead to deterioration in an individual’s daily life and social relationships. Although dopaminergic drugs can be used in the treatment of dystonia, the aim of the study was to report that these drugs may also be a factor in further development of dystonia and to attract the attention of clinicians to this anomaly.